2018
DOI: 10.1001/jamadermatol.2017.5142
|View full text |Cite
|
Sign up to set email alerts
|

Association of Facial Exercise With the Appearance of Aging

Abstract: complete remission and no adverse events were observed. However, 5 patients experienced grade 3 or 4 adverse events (1 patient had sepsis; 2, diabetes; 1, hypertension; and 2, endocrine disorders) between the initial cycle and the first rituximab maintenance infusion. At their last follow-up visit (median [range], 78 [42-147] months after the first cycle of rituximab), all 11 patients remained in complete remission, with 10 patients having discontinued rituximab maintenance therapy. Serum anti-desmoglein 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 4 publications
1
33
0
8
Order By: Relevance
“…The qualitative results from this study were less generalizable, as both external and self-evaluation of photographic results showed statistically significant improvement, in the upper lip and jawline only [10]. The remaining study by Alam et al, assessment by two blinded physicians using the Merz-Carruthers Facial Aging Photoscale (MCFAP), showed a statistically significant increase in upper (p = 0.003) and lower cheek (p = 0.003) fullness after completion of a 20-week facial exercise program, when compared to the baseline [17]. Overall, the data from these studies show the subjective improvement of facial aging changes which, when measured quantitatively, are complemented by increased muscle thickness.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The qualitative results from this study were less generalizable, as both external and self-evaluation of photographic results showed statistically significant improvement, in the upper lip and jawline only [10]. The remaining study by Alam et al, assessment by two blinded physicians using the Merz-Carruthers Facial Aging Photoscale (MCFAP), showed a statistically significant increase in upper (p = 0.003) and lower cheek (p = 0.003) fullness after completion of a 20-week facial exercise program, when compared to the baseline [17]. Overall, the data from these studies show the subjective improvement of facial aging changes which, when measured quantitatively, are complemented by increased muscle thickness.…”
Section: Resultsmentioning
confidence: 95%
“…A total of eight studies were reviewed, four of which involved facial acupuncture and four involving facial exercises [10][11][12][13][14][15][16][17]. The countries represented in the studies involving acupuncture include Korea (n = 2), Thailand (n = 1), and Japan (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature suggests that the repeated occurrence as well as transition between differing facial expressions results in a groove forming beneath the skin surface, after which fine wrinkles develop [1,2]. To lessen the development of facial wrinkles, several studies have observed that short-term facial muscle exercise training improves wrinkles and prevents sagging of the face in middle-aged and older women [3][4][5]. This may also suggest that the influence on facial soft tissue is different between facial exercises and movements of differing facial expressions.…”
Section: Introductionmentioning
confidence: 99%